Hypertensive disorders of pregnancy in Hunan Province, China, 2012–2022 - Zhou, Xu; Wu, Yinglan; Chen, Xiaoying; Jiang, Yurong (Frontiers in Medicine, 2024)
ObjectiveTo explore the relationship between hypertensive disorders of pregnancy (HDP) and adverse pregnancy outcomes and explore the risk factors for HDP.MethodsData were obtained from the Maternal Near-Miss Surveillance System in Hunan Province, China, 2012–2022. Chi-square trend tests (χ2trend) were used to determine trends in prevalence by year. Unadjusted odds ratios (uORs) were used to examine the association between HDP and adverse pregnancy outcomes. Multivariate logistic regression analysis (method: Forward, Wald, α = 0.05) and adjusted odds ratios (aORs) were used to identify risk factors for HDP.ResultsOur study included 780,359 pregnant women, and 38,397 women with HDP were identified, with a prevalence of 4.92% (95% CI 4.87–4.97). The prevalence of preeclampsia-eclampsia, gestational hypertension, chronic hypertension, and chronic hypertension with superimposed preeclampsia was 2.28% (95% CI 2.25–2.31), 2.04% (95% CI 2.00–2.07), 0.43% (95% CI 0.41–0.44), and 0.18% (95% CI 0.17–0.19), respectively. From 2012 to 2022, the prevalence of HDP increased from 3.11 to 7.39%, showing an upward trend (χ2trend = 2220.88, p < 0.01). HDP was associated with the following adverse pregnancy outcomes: maternal deaths (uOR =4.05), maternal near-miss (uOR =6.37), preterm birth (uOR =2.51), stillbirth and neonatal death (uOR =1.45), low birthweight (uOR =4.37), abruptio placentae (uOR =4.45), uterine atony (uOR =1.49), retained placenta (uOR =1.54), puerperal infections (uOR =2.14), abdominal surgical site infections (uOR =2.50), urinary tract infections (uOR =1.60), upper respiratory tract infections (uOR =1.75), heart disease (uOR =2.76), embolism (uOR =2.66), liver disease (uOR =1.25), anemia (uOR =1.38), diabetes mellitus (uOR =2.35), renal disease (uOR =4.66), and pulmonary disease (uOR =4.70, p < 0.05). Results of multivariate logistic regression analysis showed risk factors for HDP: maternal age > 30 years (aOR > 1, p < 0.05), gravidity > = 4 (aOR =1.10, 95% CI 1.05–1.14), primipara (aOR > 1, p < 0.05), and previous cesarean sections (aOR =1.27, 95% CI 1.24–1.31).ConclusionThe prevalence of HDP was relatively high in Hunan Province. HDP was associated with many adverse pregnancy outcomes. Advanced maternal age, high gravidity, primipara, and previous cesarean section were risk factors for HDP.